Circadian blood pressure rhythm and renal function in males with essential arterial hypertension - I. G. Fomina; N. E. Gaidamakina; T. A. Dyakova; A. V. Vetluzhsky (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To assess blood pressure (BP) increase type and circadian BP profile in young hypertensive men aged under 35 years. To describe the association between renal function and 24-hour BP monitoring (BPM) parameters. Material and methods. Twenty-four-hour BPM was performed in 58 patients by «SpaceLabs»device (USA), during 24 hours, with 15-minute intervals in daytime (7 AM - 11 PM), and 30-minute intervals in nighttime (11 PM - 7 AM). Dynamic angionephroscintigraphy with DTPA 99mTc was performed in all participants. Most young patients had Stage I arterial hypertension (AH) (n=51; 43%), or Stage II AH (n=49; 42%). Stage III AH was diagnosed in 18 individuals (15%). Results. Transitory AH was diagnosed by temporal index (TI) in 36 patients (72%). Stable AH with AH TI>50% was observed in 14 participants (28%). Glomerular hyperfiltration was more manifested in stable AH, comparing to transitory AH: 132.0±33.5 ml/min vs 165.57±38.5 ml/min (р=0.04). Significant difference in mean glomerular filtration rates (GFR) was observed in patients with isolated inadequate systolic BP (SBP) decrease, or simultaneous inadequate SBP and diastolic BP (DBP) decrease. In patients with disturbed SBP rhythm, hyperfiltration was observed. Circadian BP profile disturbances were associated with lower mean GFR. Conclusion. In stable AH, hyperfiltration is significantly more pronounced, that is a symptom of kidney pathology as target organ damage. Twenty-four-hour BPM helped to identify a substantial group of patients non-dippers among young males: in 60% of participants, for SBP, in 24% - for SBP and DBP. Circadian BP rhythm disturbances resulted in hyperfiltration development, and inadequate DBP decrease – in reduced GFR.